2015
DOI: 10.1016/j.msea.2014.11.061
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evolution and mechanical properties of Mg–11Gd–4.5Y–1Nd–1.5Zn–0.5Zr alloy prepared via pre-ageing and hot extrusion

Abstract: The Mg-11Gd-4.5Y-1Nd-1.5Zn-0.5Zr (wt.%) alloy was pre-aged prior to hot extrusion.Pre-ageing treatment introduced uniform distribution of plate-like Mg 5 RE precipitates, which transformed into nano-scale globular Mg 5 RE particles by split and spheroidization during hot extrusion. These globular Mg 5 RE particles contributed to continuous dynamic recrystallization by promoting the evolution of low misorientation sub-grain boundaries to high misorientation grain boundaries and caused grain refinement through g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…7d). The plate phases are similar to previously reported Mg 5 RE phase [11,12], which is also confirmed by present EDS results. Thus, the bulk LPSO/Mg 17 Sr 2 phases, both in the micron size, and plate Mg 5 RE phases in nano-scale are found to precipitate in as-extruded sample 0.2Sr.…”
Section: Methodssupporting
confidence: 92%
See 2 more Smart Citations
“…7d). The plate phases are similar to previously reported Mg 5 RE phase [11,12], which is also confirmed by present EDS results. Thus, the bulk LPSO/Mg 17 Sr 2 phases, both in the micron size, and plate Mg 5 RE phases in nano-scale are found to precipitate in as-extruded sample 0.2Sr.…”
Section: Methodssupporting
confidence: 92%
“…In the past decade, the Mg-Gd-Y-Zn based alloys containing long period stacking ordered (LPSO) structures have been shown to exhibit excellent mechanical properties, including the high tensile strength of over 500 MPa at room temperature [8][9][10][11][12]. The outstanding property can be…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it can be seen from the engineering stress-strain curves that the ECAP alloy in this work display strong work hardening effect, which suggests that the interaction between dislocations and microstructures (refined second phases, grain boundaries, and nano-precipitates) plays an important role in strengthening of the alloys [41]. The refined microstructures and increased phase boundaries or grain boundaries are effective to hinder the propagation of micro cracks, which obviously improves the toughness of the ECAP alloys.…”
Section: Mechanical Properties Of Cast and Ecap Alloysmentioning
confidence: 64%
“…2 revealed that Mg 3 RE and Mg 12 REZn phases co-existed in the cast-T4 sample. Based on the previous investigation, the LPSO phase can be identified as Mg 12 REZn [16]. The eutectic phase should be identified as Mg 3 RE or Mg 3 (RE, Zn) phase [17].…”
Section: Microstructurementioning
confidence: 99%